2022
DOI: 10.1002/jcsm.12927
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency is related to low functional outcome in patients at early rehabilitation after acute stroke

Abstract: Background Iron deficiency (ID) is a common co-morbidity in patients with cardiovascular disease and contributes to impaired functional capacity. The relevance of ID in patients in recovery after acute stroke is not known. We assessed the prevalence of ID and anaemia in relation to functional capacity and to recovery during early rehabilitation after stroke. Methods This observational study enrolled consecutively 746 patients with ischaemic or haemorrhagic stroke at in-patient early rehabilitation (age 68 ± 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Iron is an essential trace element, which plays a pivotal role in cellular metabolism, survival and proliferation (8). Several studies reported that iron deficient caused anemia, neurocognitive dysfunction, and impaired functional capacity (9,10), whereas iron overload resulted in osteoporosis, neurodegeneration, and cardiovascular diseases (11)(12)(13). In the field of skeletal muscle research, recent studies also demonstrated an association between iron status and muscle disorders in experimental animals (14,15), but the link between serum iron status and muscle mass in human is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Iron is an essential trace element, which plays a pivotal role in cellular metabolism, survival and proliferation (8). Several studies reported that iron deficient caused anemia, neurocognitive dysfunction, and impaired functional capacity (9,10), whereas iron overload resulted in osteoporosis, neurodegeneration, and cardiovascular diseases (11)(12)(13). In the field of skeletal muscle research, recent studies also demonstrated an association between iron status and muscle disorders in experimental animals (14,15), but the link between serum iron status and muscle mass in human is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Low TSAT has also been associated with low functional outcomes after IS. 32 In a cohort, which included 35 patients with acute stroke and 44 controls, it was reported that transferrin is associated with a protective role in patients with stroke. 33 In this MR study, we found that TSAT is causally related to poor outcomes after IS, and no relationship for transferrin is identified in the MR analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained from our enrolled patients underwent ROC analysis and LASSO-filtered variables to identify valuable predictive indicators, which primarily encompassed the pathophysiology of neuroinflammation, anemia, and antioxidation during the subacute stage of stroke. HGB levels are the gold standard for anemia, commonly and associated with poor outcome function after a stroke 34, 35 . The World Health Organization defines anemia as a hemoglobin level of less than 130 g/L.…”
Section: Discussionmentioning
confidence: 99%